A Time to Choose : Caribbean Development in the 21st Century - Kathuria, Sanjay; Rouis, Mustapha; Corlett, Michael; Hanson, James; Oberai, Rina H.; Tomlinson, Kevin; Ruppert Bulmer, Elizabeth; Blom, Andreas; Jha, Abhas; Nuamah, Camille; Brenzel, Logan (World Bank, Washington, DC, 2012)
The Caribbean region is at a development crossroads and its member nations must take significant and concrete steps to improve productivity and competitiveness and face up to global competition if they are to accelerate or even maintain past growth, says a new World Bank report1. By taking such steps, they will reposition themselves strategically as an emerging trading bloc for goods and services; without such action, they risk growing economic marginalization and erosion of many of the social gains of the last three decades.